Shoulder pain: a comparison of wheelchair athletes and nonathletic wheelchair users - Fullerton, H. D.; Borckardt, J. J.; Alfano, A. P. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The purpose of this study was to directly compare the onset and prevalence of shoulder pain in athletic and nonathletic wheelchair users. METHODS: A questionnaire was distributed to athletic and nonathletic wheelchair-dependent populations. This inquired about presence and duration of shoulder pain, age of subject, level of injury, duration of time since injury, wheelchair use, involvement in sports, and training habits. A total of 257 subjects were involved in the study. RESULTS: The odds of having shoulder pain were twice as high among nonathletes as they were among athletes. This finding represents a significant difference over and above age differences, differences in years spent in a wheelchair, and differences in level of spinal cord injury. Athletes also have an average of 12 yr free of shoulder pain after becoming wheelchair bound, whereas nonathletes have only 8 yr. CONCLUSION: Promotion of active exercise for wheelchair users is encouraged to decrease shoulder pain, resulting in more functional, pain-free years.